Landslide Monitoring Of Natural Terrain Area In Central Aceh Using Interferometric Synthetic Aperture Radar Techniques - Jefriza, Jefriza (2021)
Surface deformation measurements are critical for landslide studies. Interferometric Synthetic Aperture Radar (InSAR) technique is very important for landslide studies as it contributes to soil surface deformation monitoring methods for slow movement rates before landslides occur. The technique has been widely used in urban and rural areas. Landslides movement in the study area of Central Aceh, Indonesia, are mostly categorized as rapid landslides in terms of velocity rate classification. This is due to four factors which are; heavy rainfall amount, tectonic/fault zone, soft soil, and human activity (cut-slope). The objective of this study is to measure and analyze the slow deformation of landslides in the natural terrain areas. InSAR techniques can monitor this type of movement rate within large areas. Monitoring of landslides at natural altitudes will be limited to cloud problems if optical remote sensing is used. The time series of Single Look Complex Synthetic Aperture Radar (SLC SAR) of new and updated Sentinel-1 and historical data of ALOS PALSAR were used. The analyses of InSAR techniques used are Persistent Scatterer (PS), Small Baseline Subset (SBAS), and Quasi-PS (Q-PS). PS is widely used in urban, whereas SBAS and Q-PS can be applied in both urban (such as city center) and rural areas (such as undulating natural terrain areas). Exploitation and a combination of each radar image and InSAR techniques (PS and Q-PS) with an ascending or descending orbit pass with a new and an updated Sentinel-1 SAR images is a promising technique to fill the gap of each radar slant range due to shadow effect